The impact of core self-evaluations and person-job fit on work-related outcomes - Zhang, Zongguo; Yan, Zhen (Frontiers in Psychology, 2024)
The aim of this study is to explore the mediating effect of emotional exhaustion (EE) between core self-evaluations (CSE), person-job fit (PJ fit) and service recovery performance (SRP). The current research also examines whether organizational dehumanization (OD) moderates the relationship between two antecedents ， EE and SRP. We collected time-lagged and multi-source data from star-rated hotels in three cities in China. In particular, direct supervisors of frontline employees (FLEs) rated their SRP (N = 32 supervisors and their 212 immediate employees). The hypotheses were gauged via PROCESS (version 3.4). Based on conservation of resources theory (COR) theory, the results indicate that CSE and PJ fit alleviate FLEs' EE, which subsequently advances their SRP. OD moderates the direct impact of two antecedents on EE and SRP. Moreover, OD moderates the indirect influence of two antecedents on SRP through EE. Hotel management should acknowledge the significance of CSE and PJ fit. By using the CSE and PJ fit questionnaire, organizations can effectively identify candidates who possess ample resources. Since such personal characteristic and conditional resources can effectively alleviate EE, thereby improving FLEs' SRP. Besides, managers should take into account the detrimental impact of OD on FLEs' SRP and strive to foster an organizational culture that appreciates these employees both as individuals and as indispensable resources for the organization. The hospitality literature currently lacks an in-depth understanding of the underlying mechanism through which CSE and PJ fit affect FLEs' SRP. The current research incorporates EE as a mediator of the CSE's and PJ fit 's impact on SRP, and to the authors' knowledge, this study is the first to evaluate whether OD moderate the direct influence of CSE and PJ fit on SRP and the indirect impact of CSE and PJ fit on the aforementioned outcome via EE.